PENGARUH DEBT TO ASSET RATIO, QUICK RATIO, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Siti Fatimatul Munawaroh; Ika Wahyuni; Ida Subaida (Fakultas Ekonomi dan Bisnis, 2026)
The purpose of this study is to analyze and test the effect of Debt to Asset Ratio, Quick Ratio, and Sales Growth on Company Value with Profitability as an intervening variable. The objects of this study are property and real estate companies listed on the Indonesia Stock Exchange in 2022-2024. The results of the direct effect hypothesis test using the Smart PLS 3.0 application indicate that Debt to Asset Ratio has a significant negative effect on Profitability. Quick Ratio has a positive insignificant effect on Profitability. Furthermore, Sales Growth has a negative insignificant effect on Profitability and Company Value. Debt to Asset Ratio has a positive insignificant effect on Company Value, Quick Ratio has a negative insignificant effect on Company Value. Meanwhile, Profitability has a positive insignificant effect on Company Value. The results of the indirect hypothesis test indicate that the variables Debt to Asset Ratio, Quick Ratio, and Sales Growth have a negative insignificant effect on Company Value through Profitability